تأثير إضافة نفايات البولي إيثيلين في تحسين أداء الخلائط الإسفلتية المحلية - رامي الناصر (Tishreen University, 2019)
The use of recycled waste in pavement paving is a positive choice in terms of sustainability, and attractive to enhance and improve the performance of these layers, This is especially true for recycled plastics because it is made up of polymeric materials. The aim of this research is to investigate the possibility of using a type of plastic waste (LDPE) for recycling and to use it to improve the performance and properties of the asphalt mixtures of the wearing layer compared to the uncoordinated traditional mixture by laboratory work in which the optimum asphalt contect (4.8%), and then addition of polyethylene waste by (8, 10, 12, 14, 16%) ratio . Results showed that the  maximum stability values were at the addition of (12%), where the stability increased by (17.7%) with achieving the value of high marshall stiffness . The study concluded that polyethylene waste can be used as additives  for asphalt mixtures to achieve sustainable management of plastic waste and improve the performance of asphalt mixtures. يعد استخدام النفايات المعاد تدويرها في طبقات الرصف الطرقي خياراً إيجابياً من ناحية تحقيق الاستدامة ، وجذباً لتقوية وتحسين اداء تلك الطبقات ، وهذا ينطبق بشكل خاص على البلاستيك المعاد تدويره كونه يتكون من مواد بوليميرية . هدف هذا البحث التحقق من إمكانية استخدام أحد أنواع نفايات البلاستيك (البولي ايثيلين منخفض الكثافة) لإعادة تدويرها والاستفادة منها في تحسين أداء وخواص الخلائط الاسفلتية الخاصة بطبقة الاهتراء مقارنة مع الخلطة التقليدية غير المعدلة ، وذلك من خلال القيام بعمل مخبري تم فيه تصميم خلطة اسفلتية وتحديد النسبة المثالية للإسفلت (4.8 %) ، و إضافة نفايات البولي ايثيلين بنسب (8 ، 10 ، 12 ، 14 ، 16 %) ، وقياس خواص مارشال للخلائط المعدلة. بينت النتائج أن قيم الثبات العظمى كانت عند الإضافة بنسبة (12 %) حيث ازداد الثبات بنسبة (17.7%) مع تحقيق قيمة صلابة مرتفعة. خلصت الدراسة إلى أنه يمكن استخدام نفايات البولي ايثيلين كمعدل للخلائط الاسفلتية لتحقيق إدارة مستدامة  للنفايات البلاستيكية وتحسين أداء الخلائط الإسفلتية.